Study of the Coarsening of Nanoporous Gold Nanowires by In Situ Scanning Transmission Electron Microscopy During Annealing. Issue 11 (3rd September 2019) - Chauvin, Adrien; Molina-Luna, Leopoldo; Ding, Junjun; Choi, Chang-Hwan; Tessier, Pierre-Yves; El Mel, Abdel-Aziz
Abstract : Over the past decades, porous gold has been used in plenty of applications such as catalysis or sensor detection. However, the nanoscale size of both the ligaments and pores makes such material very sensible to temperature. Indeed, the increase in temperature induces coarsening of the structure which can be detrimental for various applications. In this context, understanding of the coarsening on nanoporous gold (NPG) is crucial. In this communication, in situ scanning transmission electron microscopy (STEM) analysis of coarsening is reported by considering the nanosize of the dealloyed sample in dependence on the annealing of NPG nanowire. This study is performed by the in situ STEM of NPG nanowires after annealing between 25 and 600 °C with two different feature ratios (i.e., ligament/pore size) of 0.6 and 1.4. Herein, for the first time, an experimental demonstration is carried out for the two different behaviors of morphology evolution with temperature, corresponding to ligament pinch‐off and collapsing of nanoporous materials, which have been highlighted by simulations in the literature. Abstract : The coarsening behaviors of nanoporous gold nanowires are reported for the first time by in situ scanning transmission electron microscopy (STEM) during annealing. The two mechanisms for the coarsening of nanoporous materials (i.e., ligament pinch‐off and collapsing), studied by simulation in the literature, are demonstrated experimentally here. The dependence on the feature ratio (i.e., ligament over pore size) is elucidated.